Point-Prevalence Surveys of Antibiotic Use at Three Large Public Hospitals in Kenya. (October 2020) - Omulo, Sylvia; Oluka, Margaret; Ombajo, Loice; Osoro, Eric; Kinuthia, Rosaline; Guantai, Anastasia; Ndegwa, Linus; Verani, Jennifer; Opanga, Sylvia; Wesangula, Evelyn; Nyakiba, Jarred; Makori, Jones; et al.
Abstract : Background: Antibiotics are the most prescribed medicines worldwide, accounting for 20%–30% of total drug expenditures in most settings. Antimicrobial stewardship activities can provide guidance for the most appropriate antibiotic use. Objective: In an effort to generate baseline data to guide antimicrobial stewardship recommendations, we conducted point-prevalence surveys at 3 hospitals in Kenya. Methods: Sites included referral hospitals located in Nairobi (2, 000 beds), Eldoret (900 beds) and Mombasa (700 beds). [Results are presented in this order.] Hospital administrators, heads of infection prevention and control units, and laboratory department heads were interviewed about ongoing antimicrobial stewardship activities, existing infection prevention and control programs, and microbiology diagnostic capacities. Patient-level data were collected by a clinical or medical officer and a pharmacist. A subset of randomly selected, consenting hospital patients was enrolled, and data were abstracted from their medical records, treatment sheets, and nursing notes using a modified WHO point-prevalence survey form. Results: Overall, 1, 071 consenting patients were surveyed from the 3 hospitals (n = 579, n = 263, and n = 229, respectively) of whom >60% were aged >18 years and 53% were female. Overall, 489 of 1, 071 of patients (46%) received ≥1 antibiotic, of whom 254 of 489 (52%) received 1 antibiotic, 201 of 489 (41%) received 2 antibiotics, 31 of 489 (6%) received 3 antibiotics, and 3 of 489 (1%) received 4 antibiotics. Antibiotic use was higher among those aged <5 years: 150 of 244 (62%) compared with older individuals (337 of 822, 41%). Amoxicillin/clavulanate was the most commonly used antibiotic (66 of 387, 17%) at the largest hospital (in Nairobi) whereas ceftriaxone was the most common at the other 2 facilities: 57 of 184 (31%) in Eldoret and 55 of 190 (29%) in Mombasa. Metronidazole was the next most commonly prescribed antibiotic (15%–19%). Meropenem was the only carbapenem reported: 22 of 387 patients (6%) in Nairobi, 2 of 190 patients (1%) in Eldoret, and 8 of 184 patients (4%) in Mombasa. Stop dates or review dates were not indicated for 106 of 390 patients (27%) in Nairobi, 75 of 190 patients (40%) in Eldoret, and 113 of 184 patients (72%) in Mombasa receiving antibiotics. Of 761 antibiotic prescriptions, 45% had a least 1 missed dose. Culture and antibiotic susceptibility tests were limited to 50 of 246 patients (20%) in Nairobi, 17 of 124 patients (14%) in Eldoret, and 23 of 119 patients (19%) in Mombasa who received antibiotics. The largest hospital had an administratively recognized antimicrobial stewardship committee. Conclusions: The prevalence of antibiotic use found by our study was 46%, generally lower than the rates reported in 3 similar studies from other African countries, which ranged from 56% to 65%. However, these survey findings indicate that ample opportunities exist for improving antimicrobial stewardship efforts in Kenya considering the high usage of empiric therapy and low microbiologic diagnostic utilization. Funding: None Disclosures: None